Methodological Proposal to Analyze Socioeconomic Residential Segregation Through a Synthetic Indicator (sssi) and its Application in Bogotá - Parias, Adriana (Universidad del Rosario, 2021)
Urban socioeconomic residential segregation is a persistent problem in capitalist cities. However, theorical approaches to explain this problem are limited, where sociological or geographical descriptive approaches and methodologies predominate. In this work, we propose to make operational the urban land rent theory. This presentation main purpose is to determine the level of socioeconomic segregation in Bogotá, based on the construction of an indicator that seeks to make operational the notion of segregation monopoly rent (Jaramillo, 2009), which offers an explanatory framework of this phenomenon. Our starting point is the implementation of the Socioeconomic Spatial Segregation Index (sssi), initialized by Villanueva (2018), which allows us to measure inequality in access to residential urban land, based on the relation between the population distribution and the income level, which can be used to determine a range of feasible locations (potential access to land) for each population group on the urban space of the city, given the prices of land (and built space). Thus, the presentation contributes to the understanding of the socioeconomic residential segregation and opens the debate on an original methodological device for its measurement.